European film remakes - Cuelenaere, Eduard; Willems, Gertjan; Joye, Stijn (Screen serialities., 2021)
Bringing together a range of international scholars, European Film Remakesdiscusses for the first time the textual, socio-cultural, political, and industrial mechanisms and singularities of the film remake in a European context.